POLLUTION INDEX AND ECONOMIC VALUE OF VANNAMEI SHRIMP (Litopenaeus vannamei) FARMING IN INDONESIA - Ofan Bosman; Tri Edhi Budhi Soesilo; Sinung Rahardjo (Indonesian Aquaculture Journal, 2021)
Shrimp farming has contributed a large share in Indonesia’s aquaculture portfolio for at least a decade, and a national plan to increase shrimp production by 250% has been recently laid out. However, boosting shrimp productions could lead to unintended consequences in environmental and socio-economic negative impacts. The rapid development of vannamei farming in Java has increased coastline land clearings and demands of fertilizers, feeds, and chemicals to sustain the farming activities. Such pressures will eventually lead to a reduced environmental capacity and the farming efficiency itself. This study aimed to study the environmental impacts and business performance of intensive shrimp farming in Indonesia. The study was conducted in Aquaculture Business Center (ABC) in Karawang for four months, from July to October 2020. In-situ and ex-situ measurements of water quality parameters were done at six sampling stations directly post-harvest water discharge. The measured parameters consisted of temperature, pH, dissolved oxygen, ammonia (NH3), nitrite (NO2), nitrate (NO3), phosphate (PO4), alkalinity, and salinity. Pollution Index (PI) was used as the primary method to determine the environmental impacts of the shrimp farming. The R/C Ratio was used to analyze the business performance of the company. The results showed that the water quality index in the ABC area was categorized as lightly polluted in station 1 (PIj 4.52) and station 5 (PIj 4.37), moderately polluted in station 2 (PIj 6.24), station 3 (PIj 6.72), and station 4 (PIj 6.13) and heavily polluted in station 6 (PIj 111.06). The determined R/C ratio was 1.10, meaning that the shrimp farming is classified as economically profitable. Although the shrimp farming’s economic performance value is very good, the water conditions affected by waste from the shrimp pond culture will reduce the R/C ratio in the future if not properly managed.